Clinical and laboratory characteristics of patients with COVID-19 and concomitant type 2 diabetes - T. Yu. Demidova; K. G. Lobanova; S. N. Perekhodov; M. B. Antsiferov; O. Sh. Oynotkinova (Кардиоваскулярная терапия и профилактика)
Aim. To assess the relationship between type 2 diabetes (T2D) and the course and outcomes of coronavirus disease 2019 (COVID-19), depending on clinical and laboratory parameters and comorbidities.Material and methods. A retrospective analysis of clinical outcomes was carried out in 1985 patients with documented COVID-19 who were admitted to the V. P. Demikhov City Clinical Hospital in the period from March 23, 2020 to June 01, 2020. Subsequently, 232 patients were excluded due to their transfer to another hospital. The final analysis included 1753 patients, of which 311 (17,7%) patients had T2D.Results. T2D was associated with an unfavorable outcome of COVID-19: mortality with and without — 16,1% and 7,4% (p<0,001). Age >60 years increased the mortality of patients with COVID-19, especially with concomitant T2D: patients <60 years of age without T2D — 2,2%, with T2D — 5,4% (p<0,05); patients >60 years of age without T2D — 15,6%, with T2D — 22,1% (p<0,01). Sex was not associated with mortality among COVID-19 patients. Among patients without T2D, the glycemia-depended mortality curves were U-shaped: 3,7% with glycemia <6,1 mmol/L, 1,1% with glycemia in the range of 6,17,0 mmol/L, 10,8% with glycemia >7,0 mmol/L (p<0,001). In patients with COVID-19 and T2D, a direct relationship was found between the level of glycemia and mortality: with glycemia <6,1 mmol/L, mortality rate was 8,3%, while with glycemia in the range of 6,1-7,0 mmol/L — 11,8% and glycemia >7 mmol/L — 15,6% (p<0,001). Any comorbidity worsened the outcome in COVID-19 patients. The highest mortality rate was observed in the presence of chronic obstructive pulmonary disease (46,2%; p<0,001), coronary artery disease (26,3%; p<0,001), cancer 25% (p<0,001). T2D significantly increased mortality among patients with chronic obstructive pulmonary disease — 33,3 vs 75% (p<0,05), asthma — 7,1 vs 60% (p<0,001), and cancer — 12,5 vs 62,5% (p<0,01).Conclusion. T2D is associated with unfavorable COVID-19 outcomes, especially among patients >60 years of age and high blood glucose levels. Any concomitant disease worsened the outcome of the disease. The main cause of death from COVID-19 were complications: acute respiratory distress syndrome, sepsis, acute renal failure, thrombotic events.